Effects of delayed filling and H/M Inoculant® on preservation and quality of corn silage - K. Bolsen; M. Hinds; H. Ilg; J. Hoover (Kansas Agricultural Experiment Station Research Reports, 1985)
Eight whole-plant corn silages were evaluated using laboratory silos. Treatments were: 1) control (no additive); 2) H/M Inoculant applied to the fresh crop at the forage harvester (H/M-field); and 3) H/M Inoculant applied to the fresh crop at the time of ensiling (H/M-silo). The control and H/M-field treatments were ensiled at 0, 4.5, and 12 hours post-harvest with the fresh crop remaining in the forage wagons until ensiled. The H/M-silo treatment had the inoculant applied immediately prior to ensiling at 4.5 and 12 hours post-harvest. All eight corn silages were well preserved and underwent predominantly lactic acid fermentations. H/M Inoculant did not influence lactic acid content or 1actic:acetic and lactic:DM loss ratios. However, H/M-field silage ensiled immediately showed small improvements in quality over the control silage, as judged by lactic acid content and the two fermentation efficiency ratios. H/M Inoculant did not effect DM recovery at any ensiling time. However, when averaged across inoculant treatment, silages made at 4.5 hours post-harvest had the highest DM recoveries; silages at 12 hours, the lowest. All 4.5 and 12 hour post-harvest silages had less lactic and total acids than those made at harvest. The silages made as soon as possible after harvest had a faster accumulation of lactic and total fermentation acids than the same fresh crop ensiled 12 hours post-harvest.
Keywords: Cattlemen' s Day; 1985; Kansas Agricultural Experiment Station contribution; no. 85-319-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 470; Beef; Preservation; Corn silage; Quality